Gross and Morphometrical Studies on the Soft Palate of Domestic Pig “(Sus scrofa domesticus)” - Damini V; Prasanth Babu A; Santhi Lakshmi M; Bharathi S (Indian Journal of Veterinary Anatomy, 2026)
The present study was undertaken on the soft palate of the SVVUT-17 breed of domestic pig. The soft palate extended from the posterior margin of the hard palate caudally to about the middle of the epiglottis. It was nearly horizontal in position and consisted of two surfaces, the dorsal surface (nasal surface) and the ventral surface (oral surface). The mean length of the soft palate was 5.7± 0.6 cm. The width was measured at the fixed border, at anterior pillar level, at posterior pillar level and at the free border of the soft palate and were recorded as 5.0 ± 0.4 cm, 4.4 ± 0.3 cm, 5.2±0.5 cm, 3.7 ±0.4 cm respectively. Four paired muscles, i.e., palatinus muscle, palatoglossus muscle, tensor veli palatini and levator veli palatini muscles were responsible for movement of the soft palate.